HUBUNGAN TINGKAT KECEMASAN DENGAN MEKANISME KOPING PADA PASIEN GAGAL JANTUNG KONGESTIF DI IRINA F BLU RSUP Prof. Dr. R.D. KANDOU MANADO - Djoni Ransun; Joke Pijoh; Esrom Kanine (POLTEKKES KEMENKES MANADO, 2013)
Anxiety in patients with Congestive Heart Failure caused because they experience shortness of breath and chest pain so they tend to be restless . Anxiety can motivate individuals to adapt to stressors and taking appropriate action to address them . Coping mechanism is the result of individual actions in the face of stressors . When an individual is able to face the stressor well will produce adaptive coping whereas when individuals are not able to find a good way out then will perform a maladaptive coping . This study aims to determine the relationship of the level of anxiety with coping mechanisms in patients with CHF. Descriptive research study Irina F analitik.Tempat heart , study time juni 2012 with accidental sampling technique on 30 responden.Instrumen anxiety questionnaires and questionnaires HRS - A COPE coping mechanisms. Chi Square analysis results found a significant relationship between the level of anxiety with coping mechanisms in CHF patients ( p = 0.004 < α = 0.05 ) OR = 12 Conclusion CHF patient anxiety levels shown to be associated with coping mechanisms whereby 12x experiencing mild anxiety level than the level of adaptive coping moderate anxiety. Suggestion: increase understanding of CHF patients need attention and support from family , and health practitioners in order to improve the coping mechanisms